Consensus Recommendations for the Diagnosis of Vitreoretinal Lymphoma. (3rd April 2021) - Carbonell, Denise; Mahajan, Sarakshi; Chee, Soon-Phaik; Sobolewska, Bianka; Agrawal, Rupesh; Bülow, Tanja; Gupta, Vishali; Jones, Nicholas P.; Accorinti, Massimo; Agarwal, Mamta; Batchelor, Tracy; Biswas, Jyotirmay; et al.
ABSTRACT: Purpose: To provide recommendations for diagnosis of vitreoretinal lymphoma (VRL). Methods: Literature was reviewed for reports supporting the diagnosis of VRL. A questionnaire (Delphi 1 round) was distributed to 28 participants. In the second round (Delphi 2), items of the questionnaire not reaching consensus (75% agreement) were discussed to finalize the recommendations. Results: Presenting symptoms include floaters and painless loss of vision, vitreous cells organized into sheets or clumps. Retinal lesions are usually multifocal creamy/white in the outer retina. Other findings include retinal lesions with "leopard-skin" appearance and retinal pigment epithelium atrophy. Severe vitreous infiltration without macular edema is the most likely presentation. Diagnostic vitrectomy should be performed. Systemic corticosteroid should be discontinued at least 2 weeks before surgery. An interleukin (IL)-10:IL-6 ratio > 1, positive mutation for the myeloid differentiation primary response 88 gene and monoclonality are indicators of VRL. Multi-modal imaging (optical coherence tomography, fundus autofluorescence) are recommended. Conclusions: A consensus meeting allowed the establishment of recommendations important for the diagnosis of VRL.